Impact of KRAS variant rs61764370 on breast cancer morbidity - Ustinova, M.; Daneberga, Z.; Berzina, D.; Nakazawa-Miklasevica, M.; Maksimenko, J.; Gardovskis, J.; Miklasevics, E. (Experimental Oncology, 2015)
Low-penetrance gene variants and their combinations are topical study objects in breast cancer pathogenesis. Single nucleotide polymorphism rs61764370, localized in 3՛ UTR of KRAS gene, plays an important role in the development and progression of several cancers. The aim of our study was to determine the KRAS variant impact on breast cancer morbidity. Patients and Methods: 2214 patients diagnosed with breast cancer and 861 healthy controls were screened for KRAS variant by RFLP method. Available clinical data were collected and processed using statistical analysis methods. Results of present study suggest the KRAS variant impact on breast cancer development risk in premenopausal women, but it has no effect on breast cancer prognosis. We did not observe any KRAS variant effect on breast cancer patient 10-year disease-specific survival rates. Key Words: breast cancer, rs61764370, KRAS variant, predisposing factor.